Pengaruh Kompetensi Profesional dan Gaya Mengajar Guru Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi - Sabrina Devi; Mohamad Arief Rafsanjani (Universitas Negeri Surabaya, 2021)
The aims of the research are to analyze how much influence the professional competence and teaching style of teachers have on student learning outcomes in economic subjects. This study will examine quantitative methods with a sample of 158 students from three high schools in Driyorejo district using an error rate of 5%. The technique used to collect samples is a proportional stratified random sampling technique. There are stages in data analysis, namely the classical assumption test analysis, multiple linear regression analysis, t test and test the coefficient of determination. The results of this study were the professional competence and teaching style of teachers partially positive effect on student learning outcomes in economics subjects in high schools in Driyorejo district